Peri-tumoural lymphocyte neighbourhoods predict longer survival in pancreatic ductal adenocarcinoma - Arseneau, Riley J.; Mejia, Jorge P.; Nersesian, Sarah; Lee, Stacey N.; Bekkers, Carley; Samson, Thomas; Gaston, Daniel; Gala-Lopez, Boris L.; Ramjeesingh, Ravi; Arnason, Thomas; Boudreau, Jeanette E. (Frontiers in Immunology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) remains one of the deadliest cancers and has limited options for treatment. Low immune infiltration, desmoplastic stroma, and poor tumour immunogenicity are all expected to contribute to PDAC’s rapid progression and limited response to existing immunotherapies. PDAC tumours are mosaics of different sub-tumour microenvironments, including some that do contain immune cells. We hypothesized that increasing frequency of lymphocyte:tumour interactions would correlate with lengthened survival for patients with PDAC.MethodsUsing multiplex immunofluorescence, digital pathology, and computational analyses, we profiled the spatial distribution, co-localization, and neighbourhood architecture of immune cells in tumours from 73 patients with PDAC.ResultsHigher densities of CD3+CD8– (CD4+) T cells were associated with improved five-year overall survival, particularly when enriched at the tumour-stroma boundary (i.e. peritumoural). CD3+CD8– T cells, CD8+ T cells (CD3+CD8+), and B cells (CD20+) frequently co-infiltrated and co-localized, forming distinct immune neighbourhoods indicative of organized adaptive immunity. We defined three common immune neighbourhoods within PDAC (1) Macrophage dominant; (2) T cell dominant; and (3) Disorganized. With greater tumour and peri-tumoural area represented by the T cell dominant neighbourhood, overall survival was increased. The other neighbourhoods were not significantly associated with outcomes.ConclusionImmune cells self-assemble into recurring patterns in PDAC. The presence of T cell dominant neighbourhoods, which we interpret as supporting ongoing immune activation, best predict lengthened survival. Spatially organized immune interactions may serve as prognostic indicators and inform future studies for immunotherapies in PDAC.